A Simplified Calculation Method for the Near-Slope Laterally Loaded Pile Based on a Passive Wedge Model - Minghui Yang; Bo Deng; Yuhui Wang (Advances in Civil Engineering)
When a pile is placed near the slope, the lateral loading capacity of the pile decreases significantly due to the weakening effect of soil resistance near the slope. As such, a modified soil passive wedge model for near-slope laterally loaded piles is presented to consider the weakening effect in this paper. According to development depth of different wedges, the shapes of soil passive wedge can be classified into three sorts, so as to fully analyze the influence of the slope shape and the distance from the pile center to the slope crest. On this basis, a concept of equivalent depth is proposed considering the differences of laterally loaded piles near the slope and in the horizontal ground. Besides, the unit ultimate soil resistance, which can be obtained along the different depths of pile, is introduced into the p-y curve of the soil, for achieving solution methods of internal force and displacement of laterally loaded piles under the slope weakening effect. The results of laboratory model and field tests on laterally loaded piles are compared with the proposed method, demonstrating its validity and accuracy. Furthermore, the influence of the near-slope distance on the loading capacity of the pile is fully analyzed in detail, indicating the critical near-slope distance is increasing with the increase of the undrained strength, while independent of the slope angle.